1965
DOI: 10.2134/agronj1965.00021962005700020014x
|View full text |Cite
|
Sign up to set email alerts
|

Competition for Nodule Sites Between Strains of Rhizobium japonicum Applied as Inoculum and Strains in the Soil1

Abstract: Synopsis Strains of Rhizobium japonicum applied as inoculum at different rates and by different methods differed greatly in the proportion of nodules produced on soybeans (Glycine max (L.) Merr.) grown in soils containing effective soybean rhizobia. The percentage of nodules produced by all strains applied at the standard rate of inoculation was low and averaged 5%. Increasing the amount of inoculum applied increased the percentage of nodules produced by some strains but had little effect on others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
61
0
2

Year Published

1981
1981
1988
1988

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 3 publications
6
61
0
2
Order By: Relevance
“…Johnson and Means (1964) observed that strains of soybean rhizobia tested in the greenhouse for relative com petitiveness had the same relative competitiveness to each other when used as inoculum for soybeans planted in rhizobia free soil in the field. However, Johnson et al (1965) found that strains previously shown to be of similar competitiveness in the greenhouse did not maintain the same relationship when added to soils with established populations of R. japonicum. For instance, 2 strains of lower competi tiveness than a third strain in the greenhouse formed 82% and 8% of the nodules on soybeans in competition against a native population in the field.…”
Section: Competition Between Strains Of Rhizobia For Nodule Sitesmentioning
confidence: 86%
See 4 more Smart Citations
“…Johnson and Means (1964) observed that strains of soybean rhizobia tested in the greenhouse for relative com petitiveness had the same relative competitiveness to each other when used as inoculum for soybeans planted in rhizobia free soil in the field. However, Johnson et al (1965) found that strains previously shown to be of similar competitiveness in the greenhouse did not maintain the same relationship when added to soils with established populations of R. japonicum. For instance, 2 strains of lower competi tiveness than a third strain in the greenhouse formed 82% and 8% of the nodules on soybeans in competition against a native population in the field.…”
Section: Competition Between Strains Of Rhizobia For Nodule Sitesmentioning
confidence: 86%
“…Burton (1967) reported that approximately 73,000 rhizobia were supplied per seed by the commercial rate of inoculation. Johnson et al (1965) found that the recovery of inoculum strains in the nodules of soybeans was higher in a green house experiment than it was in the field. The field ex periment was performed during the summer but soil was collected in the winter from the same field for the green house experiment.…”
Section: Competition Between Strains Of Rhizobia For Nodule Sitesmentioning
confidence: 89%
See 3 more Smart Citations